Disorder specific rewarding stimuli in anorexia nervosa. Issue 8 (6th May 2021) - Kogel, Ann‐Kathrin; Herpertz, Stephan; Steins‐Loeber, Sabine; Diers, Martin
Abstract: Objective: To enhance our understanding of reward stimuli in anorexia nervosa (AN) and to provide a basis for future research on reward processes, disorder specific reward stimuli as well as primary and secondary reinforcers were investigated. Method: We developed a set of pictures with "disorder specific reward" stimuli, with the six subcategories "sport, " "losing weight, " "healthy food, " "discipline, " "thin bodies, " "appreciation of others, " and evaluated reward ratings of these "disorder specific reward" stimuli as well as "erotic, " "high caloric, " and "neutral" stimuli in 25 patients with AN and 25 participants in the comparison group (CG). Results: We found a significant main effect for picture category and a significant interaction. The reward ratings were higher in patients with AN compared with CG for the "disorder specific reward" stimuli. In the reward subcategories, patients with AN had higher reward ratings compared with CG in all categories except of healthy food. The "disorder specific reward" stimuli of the categories "sport, " "losing weight, " and "healthy food" showed higher reward ratings compared with the categories "discipline, " "thin bodies, " and "appreciation of others" in patients with AN. Discussion: The previously used category "thin bodies" used to investigate the reward system might be less effective compared with stimuli from the categories "sport, " "losing weight, " and "healthy food."